A preliminary analysis for selecting the best hydrological probability density functions of annual peak flows associated to various return periods in some rivers of Colombia (2021)
Analysis of extreme events of annual flow peaks are used for sizing hydraulic structures for specified return period. Cumulative distribution functions are applied to annual flow peak records in order to obtain extreme values with different return periods. In Colombia, when performing a frequency analysis, hydrological planners often do not know a priori the best cumulative distribution function for making analysis. In the present research, annual flow peak records from 49 hydrometric stations located in important rivers were collected, with the objective of determining the most representative cumulative distribution function. The best results were achieved using the generalized extreme value (GEV) cumulative distribution function with the maximum likelihood method